2020
DOI: 10.1002/ijc.33138
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal signatures in cancer

Abstract: Despite advances in the treatment of solid tumors, the prognosis of patients with many cancers remains poor, particularly of those with primary and metastatic brain tumors. In the last years, "Cancer Neuroscience" emerged as novel field of research at the crossroads of oncology and classical neuroscience. In primary brain tumors, including glioblastoma (GB), communicating networks that render tumor cells resistant against cytotoxic therapies were identified. To build these networks, GB cells extend neurite-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 152 publications
(413 reference statements)
2
20
0
Order By: Relevance
“…Expression of neuronal genes has now been found not only in the brain and neuroendocrine tumors, but also in some cancers of epithelial origin (breast, ovary, colon) 65 . In recent years, it has become clear that tumor cells exploit neuronal and neurodevelopmental pathways to proliferate, migrate, and interact with normal cells, including endothelial cells and neurons 65 , 66 . Therefore, the overexpression of neuronal genes that we found in subtype 2 tumors may contribute to the aggressiveness of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of neuronal genes has now been found not only in the brain and neuroendocrine tumors, but also in some cancers of epithelial origin (breast, ovary, colon) 65 . In recent years, it has become clear that tumor cells exploit neuronal and neurodevelopmental pathways to proliferate, migrate, and interact with normal cells, including endothelial cells and neurons 65 , 66 . Therefore, the overexpression of neuronal genes that we found in subtype 2 tumors may contribute to the aggressiveness of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between tumors and the nervous system has been suspected for a long time (since Galen in the 2nd century AD) [ 3 ], because of several observations such as the effects of stress on cancer progression, the high innervation of tumor tissues, or the influence that neurotransmitters have on tumorigenesis [ 4 , 5 ]. New evidence strongly suggests the neuronal system is a key player in cancer initiation, progression and dissemination [ 5 , 6 ]. It is believed that in the same way that the nervous system can influences growth, development, and maintenance in normal tissue [ 7 , 8 , 9 ], it can contribute to the development and spread of cancer [ 5 , 10 , 11 ].…”
Section: Overview Of Tumor-nerves Interactions’ Main Componentsmentioning
confidence: 99%
“…There are several sources of nerves in cancer tissue, including nerves already present in tissue before the transformation of normal tissue cells into cancer, phenotypically transformed neurons that innervate the tissue of tumor origin [ 119 ], new branches of nerves growing to the tumor tissue from nerves localized around the tumor tissue, and axons of new neurons migrating from a distant part of the central or peripheral nervous system into the tumor tissue or its vicinity [ 120 ]. The main stimuli for the ingrowth of new nerves into cancer tissue are nerve growth factors released by cells in the tumor microenvironment [ 121 ].…”
Section: Drugs Reducing Density or Activity Of Nerves Innervating Cancer Tissuementioning
confidence: 99%
“…Signals, in the form of action potentials transmitted along the axons of autonomic and sensory neurons, participate in the modulation of cancer growth, as well as in the modulation of nervous system function by cancer. Besides electrical signals transmitted along axons, it has been shown that cancer cells may develop neurite-like protrusions that form contact with nerve endings [ 121 ], and that voltage-gated sodium channels play a role in cancer cell invasion and metastasis [ 138 , 139 ]. Therefore, it might be hypothesized that modulation of the electrical properties of cancer tissue and its vicinity might affect its progression.…”
Section: Drugs Reducing Density or Activity Of Nerves Innervating Cancer Tissuementioning
confidence: 99%